2022
DOI: 10.1002/ijch.202200030
|View full text |Cite
|
Sign up to set email alerts
|

The Systems Chemistry of Nucleic‐acid‐Peptide Networks

Abstract: Living cells use chemical building blocks (biopolymers) to form fascinatingly complex architectures, which in turn display multiple functions necessary for the cell life cycle. The mechanisms and order of events by which forerunners of these extant biopolymers formed on the early earth remains under intensive investigation. Prebiotic chemistry research has recently provided ample evidence that both peptide and nucleic‐acid (NA) precursors could be formed in a primordial environment through common synthetic rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…While self-organizing systems based separately on NA and peptides have been extensively explored, 7 studies on the self-assembly of NA-pep chimeras were only initiated in recent years. 8 These assays revealed that the NA-pep assembly can provide access to new architectures, but at the same time that it is difficult to predict and control the outputs, since complex web of interactions govern the kinetics and thermodynamics of such processes. 2 h , j ,6 b ,9 Accordingly, we have systematically developed reversible self-assembly reactions to tune the formation of NA-pep materials and to find ways for satisfying the multiple interaction interfaces affecting the assembly structures.…”
Section: Introductionmentioning
confidence: 99%
“…While self-organizing systems based separately on NA and peptides have been extensively explored, 7 studies on the self-assembly of NA-pep chimeras were only initiated in recent years. 8 These assays revealed that the NA-pep assembly can provide access to new architectures, but at the same time that it is difficult to predict and control the outputs, since complex web of interactions govern the kinetics and thermodynamics of such processes. 2 h , j ,6 b ,9 Accordingly, we have systematically developed reversible self-assembly reactions to tune the formation of NA-pep materials and to find ways for satisfying the multiple interaction interfaces affecting the assembly structures.…”
Section: Introductionmentioning
confidence: 99%